PENGARUH PENGGUNAAN MODEL PEMBELAJARAN INSIDE OUTSIDE CIRCLE TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS 4 DI MI TARBHIYATUSSHIBYAN - Melani Hildayanti; Santi Lisnawati; Syarifah Gustiawati (Fakultas Agama Islam Universitas Ibn Khaldun Bogor, 2018)
The purpose of this research is to know the influence of the use of Inside Outside Circle learning model to the learning result. In this study using experimental research method is part of quantitative method, and has its own characteristics especially with the control group and experimental group. Based on data analysis of research result, it can be concluded that: (1) The result of learning of Indonesian 4th graders in MI Tarbiyatusshibyan in experimental class by using Inside Outside Circle learning model got the average result of 82,86 and control class without using Inside Outside Circle gets 69.52 results. (2) There is a difference in the use of Inside Outside Circle learning model to the learning outcomes of grade 4 students at MI Tarbiyatusshibyan. This is shown based on the recapitulation of t test results obtained in both learning that exceeds t table with a significance level of 0.05, that is experimental class learning using Inside Outside Circle learning model has a larger t test result -15.339 than control class learning without using the Inside Outside Circle learning model of -11.306. Thus it can be concluded Ha accepted and Ho rejected that there are differences in learning outcomes are significant between the experimental class and control class.